Communication of Adolescents on Sexual and Reproductive Health Issues with their Parents in Selected Public Schools of Jhapa - Bhandari, Menuka; Rimal, Sarmila (Curriculum Development Journal, 2023)
Adolescence is a vulnerable period and adolescents are at higher risk of sexual and reproductive health problems, abuse, violence, and suicide. Thus, parents have an influential role in helping them throughout this phase of sexual maturation through open communication. Many studies have shown poor communication in a global context as well as in Nepal. Therefore, the objective of this study was to assess the communication of adolescents on sexual and reproductive health issues with their parents in selected public schools of Jhapa. This study was a descriptive cross-sectional study conducted in 210 students of classes 9 and 10 of Shree Buddha Adarsha Secondary School, Buddhashanti-1 Jhapa, Nepal. Non-probability purposive sampling was used to select the setting and the study population. Self administered semi-structured questionnaires were used for data collection and data entry was done in SPSS version 16.0. The data was analyzed using descriptive and inferential statistics. The findings of the study revealed that the level of communication of adolescents on sexual and reproductive health with their parents was low in the majority of respondents (90.0%). However, two-thirds (72.4%) of respondents had the average quality of communication followed by a high of 1.0%. Therefore, findings suggested that even though most students were positive towards the importance of sexual reproductive health communication with parents, most of them were not communicating well and topics such as abortion, pregnancy, homosexuality, and fertilization were highly avoided.